Faneuil Hall Market, ca. 1880 - Meade, Dodge and Company (Tufts Archival Research Center, 2005)
Elevated view west of Faneuil Hall Market, located on Commercial Street between North and South Market Streets. Signage adorns the southeast corner of the market as well as its columned facade, which faces east. Awnings and covered booths line the south elevation of Faneuil Hall Market, which faces South Market Street. The east elevation of Faneuil Hall is included along the upper-left side of the photograph. Several pedestrians and horse-drawn wagons fill North Market and Commercial Streets. 6 7/16 x 8 7/16, 7 x 9 overall Cabinet photographs